USER EXPERIENCE EVALUATION ON USE OF COSMETIC BUSINESS TO CONSUMER (B2C) E-COMMERCE SITES - Puspasari, Maya Arlini; Sari, Tiara; Pratama, Fariz Setyana; Fadillah, Muhammad Farhan (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2019)
The development of technology in connectivity makes significant increase of online transactions. The online transaction in cosmetics takes the third place of all online transactions in Indonesia. Many business people dealing in cosmetics to switch to online business, known as electronic commerce (e-commerce). There are 3 types of e-commerce: Business to Consumer (B2C), Business to Business (B2B), and Consumer to Consumer (C2C). E-commerce site B2C type is the biggest e-commerce transaction. The tough competition in Indonesia has made the B2C sites suffer loss in the competition to the C2C sites. Use of a site is closely related to user experience. This research aims to evaluate the user experiences of two B2C sites, i.e. SE and SO as well as the C2C site SH. This research was done by giving scenario Taska in line with the available features. Based on the research, SH was superior compared to SE and SO.